Melancholia and Traumatic Reenactment in Contemporary American Fiction: A Caruthian Reading of Gillian Flynn's Novels - Safari Monfared, Mahdi; Zarei , Erfan; Ahmadzadeh Heravi , Shideh (Journal of English Language Teaching, Literature and Culture, 2023)
Gillian Schieber Flynn's fiction is laced with such recurring themes as dysfunctional nature of families, childhood abuse and neglect, and tragic murder of the loved ones. The current study, therefore, will set out to prove that the central characters of Flynn's Sharp Objects, Dark Places, and Gone Girl have been traumatized in their childhood, the effect of which still haunts them through hallucinations, traumatic flashbacks, and nightmares. It will be contended that the characters are still melancholic after many a year, thus fixated on past traumatic events, which they reenact through diverse psychological phenomena. In addition, it will be averred that the traumas of individuals and a collective body of people are ineluctably intertwined with each other in Flynn's fiction; consequently, not only are the characters' traumas transferred to the other members of society, but also the collective trauma of fictional communities gets transmitted into the private sphere of characters' lives. To that end, the article will have recourse to Cathy Caruth's trauma theory and terminology as the underpinning theoretical framework of the foregoing study. Furnishing a novel Caruthian reading of Flynn's novels, the current research intends to contribute to the existing literature addressing the said author's narratives.